Pengembangan Sistem Informasi untuk Pegawai Berbasis Android dengan menggunakan Arsitektur Multi-Tier (Studi Kasus PT Gandum Malang) - Faris Tri Utomo; Djoko Pramono; Lutfi Fanani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT Gandum company is a cigarette manufacturer company located in Malang City. The company has three offices that are used to produce cigarettes. With different office locations, making information delivery less efficient. From the results of interviews with related parties in PT Gandum. With different office locations, the HR department in managing employee data has a problem because, if there is a change in personal data, the employee does not report to the HR department so that the data in other parts is not updated. And in conveying information by the HR department to other parts is also not efficient, because it must come to every part of each office. The results of this study are in the form of an information system that makes it easier for employees to access and manage information related to their data and information from companies and also makes it easier for the HR department to convey information to other employees. This system is built using a multi-tiered architecture where the interface side, program logic, and database are in different locations. The methodology used in this study is a prototype model. For analysis and system design illustrated by using UML diagrams (Unifed Modeling Language). The system is divided into 2, which is based on android and web-based. On Android-based systems run on smartphones for employees and computers for admin in the form of a web-based system.